THE STUPID LIBIDO: SEARCHING FOR THE ROOT CAUSES OF SEXUAL VIOLENCE AGAINST CHILDREN IN INDONESIA - Khoirul Rosyadi (Proceedings of The ICECRS, 2016)
The purpose of the present study was to explore and comprehend sexual violence against children in Indonesia using the phenomenological method. The study was conducted in Nanggroe Aceh Darussalam and West Java Provinces. In-depth interviews were carried out with several informants ranging from government officials, women activists, teachers, and community leaders. Results showed that sexual violence against children was actually perpetrated by the person closest to the victims. The perpetrators used the weakness of victims who did not dare tell their parents about the abuse, which was due to cultural and structural problems.